A comparative study on alcohol-preferring rat lines: effects of deprivation and stress phases on voluntary alcohol intake - Vengeliene, Valentina; Siegmund, Sören Volker; Singer, Manfred V.; Sinclair, John David; Li, Ting-Kai; Spanagel, Rainer (Alcoholism, 2003)
Background: Voluntary alcohol intake in rats can be influenced by alcohol deprivation phases and stress. We investigated the magnitude of the effects of both deprivation and stress (forced swimming in cold water and foot-shock had been chosen as stressors distinct in their physical and psychological features) on alcohol intake and the influence of these experiences on the time course of alcohol drinking behavior. For the alcohol drinking procedure, a long-term model of alcohol self-administration originally developed for heterogeneous Wistar rats was used and was compared with different alcohol-preferring rat lines. Methods: Adult male Alko alcohol (AA), alcohol-preferring (P), high-alcohol-drinking (HAD), and unselected Wistar rats were given ad libitum access to water, 5%, and 20% alcohol solutions for 6 months. A deprivation phase of 14 days was performed after 8 weeks of access to alcohol. After 16 weeks and 22 weeks of alcohol access, all animals were subjected to forced swimming and foot-shock, respectively, for 3 consecutive days, while alcohol intake was still being measured. Results: Alcohol deprivation led to a significant increase in alcohol intake in Wistar rats and P rats. No alcohol deprivation effect was observed in HAD and AA rats; after deprivation, however, their preference for the 20% alcohol solution increased, immediately in the HAD rats and gradually over time in the AA rats. Repeated swim stress caused an increase in alcohol intake in Wistar rats but no changes in the alcohol-preferring rat lines. Foot-shock stress increased alcohol consumption in all lines of rats, but the most pronounced effects were observed in HAD and P rats. Conclusions: Wistar, HAD, P, and AA rats differentially respond to alcohol deprivation and stress, showing that the genetic background of these different rat lines profoundly affects relapse-like drinking and stress-induced drinking.